Excreta Deposition on Grassland Patches. II. Spatial Pattern and Duration of Forage Responses. Issue 2 (1st March 2013) - White‐Leech, R.; Liu, Kesi; Sollenberger, Lynn E.; Woodard, Kenneth R.; Interrante, Sindy M.
ABSTRACT: Forage dry matter harvested (DMH) and nutritive value (NV) are affected by livestock excreta. Efforts to model nutrient cycling in grazed grasslands would benefit from increased understanding of the duration and spatial pattern of excreta effects on grassland patches. These responses were measured on 'Pensacola' bahiagrass ( Paspalum notatum Flüggé) swards treated with two excreta types (dung and urine) from two excreta source pastures (Average and High management intensities based on N fertilizer and stocking rates) applied at four frequencies (0, 1, 2, 3 per year) during 2 yr. Forage DMH under dung pats decreased, but DMH surrounding the pat was not affected by application frequency. Suppression of DMH by dung was ≥112 d and extent of suppression increased as application frequency increased. In contrast, DMH under urine increased linearly (2950 to 6250 kg ha− 1 for the Average management intensity and 3480 to 6450 kg ha− 1 for the High management intensity) as application frequency increased and effects were observed 15 cm beyond the deposit's edge. Forage NV was not affected by dung, but it increased with increasing urine application frequency and for distances up to 30 cm from the edge of the urine deposit. Urine increased DMH for ≥84 d and increased crude protein for ≥28 d following a single urine application and ≥84 d after multiple applications. Data show that duration and spatial patterns of forage response to dung and urine differ, but effects of both can be long lived and are increased by multiple deposits to a patch.